THEORY AND DESIGN OF A FLEXIBLE TWO-STAGE WIDEBAND WILKINSON POWER DIVIDER - Saxena, Antra; Hashmi, Mohammad S.; Banerjee, Deepayan; Chaudhary, Muhammad Akmal (MDPI, 2021)
This article presents the design scheme of a wideband Wilkinson Power Divider (WPD) with two-stage architecture utilizing quarter-wave transmission lines and short-circuit stubs. The bandwidth of the proposed WPD is flexible and can be controlled using the design parameters. The proposed design achieves excellent isolation between output ports in addition good in-band performance. The analysis of the proposed circuit results in a simplified transfer function which is then equated with a standard band-pass transfer function to determine the parameters of transmission lines, stub’s impedances, and the value of the isolation resistors. Furthermore, it is also demonstrated that a simple alteration in the proposed circuit enables the design of a wideband DC isolated WPD that maintains a good in-band and isolation performance. A number of case studies have been included to highlight the flexibility of the proposed design. Two distinct prototypes are developed on different boards to demonstrate the wideband performance of the proposed design. An excellent agreement between the experimental and measured results for both the designs over a wide band including very good isolation between ports validate the proposed design. Keywords: wideband; wilkinson power divider; band-pass filter; DC isolation
Keywords: Type of access: Open Access; Research Subject Categories::MEDICINE; wideband; wilkinson power divider